2016
DOI: 10.1121/1.4961163
|View full text |Cite
|
Sign up to set email alerts
|

Auditory categories with separable decision boundaries are learned faster with full feedback than with minimal feedback

Abstract: During visual category learning, full feedback (e.g., "Wrong, that was a category 4."), relative to minimal feedback (e.g., "Wrong."), enhances performance when the relevant dimensions are separable. This pattern is reversed with inseparable dimensions. Here, the interaction between trial-by-trial feedback and separability of dimensions in the auditory domain is examined. Participants were trained to categorize auditory stimuli along separable or inseparable dimensions. One group received full feedback, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Second, the feedback after each trial indicated not only whether the response was correct or incorrect—as is typical for a discrimination task—but also provided the names of the target and foil intervals. This joint feedback may have facilitated the formation of musical-interval categories, potentially by targeting a rule-based learning system for which such feedback can facilitate category learning (Ashby & Maddox, 2005, Yi & Chandrasekaran 2016). Third, on a given trial, compared to the pitch ratio of the target interval (a 4 th ), the pitch ratio of the foil interval could be either smaller (a 4 th vs. a 3 rd ) or larger (a 4 th vs. a 5 th or 6 th ), rather than consistently larger as in the tasks typically used to assess pitch-ratio discrimination (Burns & Campbell, 1994; Burns & Ward, 1978; McDermott et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the feedback after each trial indicated not only whether the response was correct or incorrect—as is typical for a discrimination task—but also provided the names of the target and foil intervals. This joint feedback may have facilitated the formation of musical-interval categories, potentially by targeting a rule-based learning system for which such feedback can facilitate category learning (Ashby & Maddox, 2005, Yi & Chandrasekaran 2016). Third, on a given trial, compared to the pitch ratio of the target interval (a 4 th ), the pitch ratio of the foil interval could be either smaller (a 4 th vs. a 3 rd ) or larger (a 4 th vs. a 5 th or 6 th ), rather than consistently larger as in the tasks typically used to assess pitch-ratio discrimination (Burns & Campbell, 1994; Burns & Ward, 1978; McDermott et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The pairs of dimensions were chosen because they are thought to be similarly complex, have independent neural representations (Schönwiesner & Zatorre, 2009), and are processed similarly in working memory (Visscher et al, 2007). Further, categorization with these perceptual dimensions has been examined in separate individuals (Maddox et al, 2003;Rabi & Minda, 2014;Yi & Chandrasekaran, 2016).…”
Section: Stimulimentioning
confidence: 99%
“…The application of the COVIS model to the auditory modality has generally demonstrated clear parallels between auditory and visual category learning mechanisms (Chandrasekaran, Koslov, et al, 2014;Chandrasekaran, Yi, et al, 2014;Reetzke, Maddox, & Chandrasekaran, 2016;Yi et al, 2014;Yi & Chandrasekaran, 2016).…”
Section: Developmental Trajectory Of Perception Of Dimensionsmentioning
confidence: 99%